Drainage and demineralisation of model cheeses made from reverse osmosis concentrates. (April 2020) - Fournier, Isabelle; Britten, Michel; Pouliot, Yves
Abstract: The impact of reducing concentrate pH, curd washing and use of trisodium citrate (TSC) to promote drainage and demineralisation in full-fat cheeses made from reverse osmosis (RO) concentrates and ultrafiltration (UF) concentrates were compared in model cheeses. Cheeses made from RO concentrate showed higher yields, mainly due to their higher lactose content. Curd washing with water decreased fat recovery and reduced cheese yields. Curd washing with TSC decreased protein and fat recovery, also negatively impacting cheese yield. Dry salting with TSC decreased protein recovery but increased fat recovery. Reducing the pH of RO concentrates decreased the total calcium content of the model cheese, and increased curd drainage, moisture adjusted cheese yield and fat recovery. Lowering the pH of both UF and RO concentrates improved their cheesemaking properties by reducing the mineral content of the casein network and increasing curd drainage and fat recovery.